Analysis of South African venture capital practitioners' views on the motivations, benefits and constraints of international syndication - Causey, John P (University of Cape Town, 2014)
Includes bibliographical references. === The international syndication of venture capital investments has become an increasingly widespread phenomenon, but there is a lack of research which applies the already limited prior international research in this field1 to South Africa or other African countries. This research aims to begin that discussion, and take the first step in filling that gap of understanding. The main research questions addressed in this study: are local venture capital practitioners ready and willing to syndicate internationally, and what are the constraints to the formation of those transactions? The issues were examined by interviewing high level investment practitioners representing seven of the 21 nongovernmental VC firms belonging to the South African Venture Capital Associated (SAVCA). This data were influenced and shaped by other available sources of primary and secondary data. The results indicate that South African venture capital investors are ready and willing to syndicate internationally, however there are caveats to that broad statement which the ensuing analysis addresses. Additionally, it was found that there are significant and profound constraints to these transactions forming in South Africa. Those constraints are an unsupportive regulatory environment, negative perceptions by the international investor community of South Africa, small domestic deal sizes and the dearth of bankable ventures led by high quality management teams. Options for further research include a study of the attitudes of potential foreign VC professional partners to the option of syndication involving South African VC firms, and a more in depth investigation into the risks and constraints to South Africa-international syndication.